One Property of Ring Q-Homeomorphisms With Respect to a p-Module - Salimov, R. R. (Ukrains’kyi Matematychnyi Zhurnal, 2013)
We establish sufficient conditions for a ring Q-homeomorphisms in \( R ^n \) , n ≥ 2, with respect to a p-module with n − 1